The Environmental Performance of Civil Employees in Sidoarjo District Based on Ethical Leadership, Ethical Climate, and Climate Strength - Tatag Herbayu, Tatag Herbayu L; Ayoub Gougui; Fareed, Abid (Journal of Islamic Economics Perspectives, 2021)
Ethical climate in several studies differently suggests likely to have a clear understanding of developing ethical behavior to be expected to their organization. Contribution to work behavior as evidence and indicating among employees tend to lead by ethical code. Hierarchy way from highest to the lowest position must lead to work together and construct developing an ethical climate. Thus, this conservative way could be the efficient and most expected value on the organization. In this research, the ethical climate is implemented by the environmental performance results of the civil servant in the Sidoarjo district. This research-based on three variable concepts by each ethical climate, ethical strength, and ethical leadership. This research utilizes a qualitative comparative method with collecting data as a literature study. The Index Satisfaction of Civil Servant in Sidoarjo District as the prime references compared to the issues and variables.